A commentary on selected speeches of Isaios - Isaeus, approximately 420 B.C.-approximately 350 B.C.; Griffith-Williams, Brenda (Leiden ; Boston : Brill, 2013)
In 'A commentary on selected speeches of Isaios', Brenda Griffith-Williams offers a fresh insight, accessible to non-Greek readers, into four disputed inheritance cases from the Athenian courts in the 4th century B.C. The only comprehensive English language commentary on Isaios (Wyse, 1904) reflects a negative view of the Athenian legal system as one in which the judges, who had no legal training, could be easily outwitted by an unscrupulous speechwriter with no regard for the truth. By addressing the complex interplay of factual, legal, and rhetorical issues in the selected speeches, Brenda Griffith-Williams identifies the strengths and weaknesses of each speaker's case and presents a more balanced assessment of Isaios's work.
Preliminary Material -- General Introduction -- Isaios 7: On the Estate of Apollodoros -- Isaios 8: On the Estate of Kiron -- Isaios 9: On the Estate of Astyphilos -- Isaios 10: On the Estate of Aristarkhos -- Appendix: Catalogue of Contested Court Hearings in Athenian Inheritance Disputes -- Glossary -- Bibliography -- General Index -- Index of Ancient Sources.
Revision of the author's doctoral thesis, University of London - 2009.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Isaeus, -- approximately 420 B.C.-approximately 350 B.C. -- Translations into English; Isaeus, -- approximately 420 B.C.-approximately 350 B.C.; Inheritance and succession (Greek law); Inheritance and succession -- Greece -- Athens -- History -- To 1500.; Forensic orations -- Greece -- Athens -- History -- To 1500.; Speeches, addresses, etc., Greek -- Translations into English; Successions et héritages (Droit grec); LAW -- Essays; LAW -- General Practice; LAW -- Jurisprudence; LAW -- Paralegals & Paralegalism; LAW -- Practical Guides; LAW -- Reference; Forensic orations; Inheritance and succession; Inheritance and succession (Greek law); Speeches, addresses, etc., Greek; Greece -- Athens; To 1500; History; Translations